Servicescape of Casual Dining Restaurants in Rinconada, Philippines - Bulalacao, Rosalie B.; Repatacodo, Jairo N. (The Indonesian Institute of Science and Technology Research, 2025)
Despite the escalating popularity, one of the most common reasons for casual dining restaurant failure is the inability to fulfill the servicescape expectations and experiences of its customers. This study determined the servicescape of casual dining restaurants in Rinconada. More specifically, the study presents the demographic profile of respondents in terms of age, gender, marital status, highest educational attainment, monthly income and frequency of visits. Assess the casual dining restaurant servicescape expectations and perceptions of customers along with ambient conditions, spatial layout, décor, signs, symbols and artifacts. Quantitative correlational research design and descriptive methods with an adopted questionnaire were used in the study. Stratified Random Sampling was used with 395 respondents that are customers of registered and DOT Accredited restaurants. That there is a highly significant relationship exists between servicescape expectations and perceptions of customers where the greater the expectation the better the perception. The proposed recommendations are deemed necessary as they serve as a tool for casual dining restaurants to create consistent, high-quality, and customer-centric environments that contribute to overall business success and competitiveness.